Empathy and burnout in Slovenian family medicine doctors: The first presentation of jefferson scale of empathy results - Penšek Lea; Selič Polona (Sciendo, 2018)
Study aimed to assess the burnout prevalence and level of empathic attitude in family medicine doctors (FMDs) and its associations with demographic factors, working conditions and physician health, using the Jefferson Scale of Empathy - Health Professional version (JSE-HP).